Spatial and spatio-temporal analysis of cancer mortality in Iran: gender disparities and implications for health policy - Alireza Zangeneh; Arash Ziapour; Seyede Negin Hoseini; Babak Nazari; Homa Molavi; Farid Najafi; Ardeshir Khosravi; Reza Heidari Moghadam (Preventive Medicine Reports)
Objectives: Cancer mortality, particularly for gender-specific cancers, has increased in Iran and other developing countries, highlighting notable disparities in regional trends and patterns. This study examines geographical and temporal trends in cancer mortality from 2017 to 2019. Methods: We analyzed data from Iran's Ministry of Health's death registration system, focusing on populations of 11,807 females and 14,450 males in 2017; 3133 females and 4439 males in 2018; and 4799 females and 6624 males in 2019. We employed spatial statistical methods, including Anselin Local Moran's I and Hot Spot Analysis (Getis-Ord Gi*), alongside techniques such as Mean Center, Standard Distance, and Geographic Information Systems to evaluate cancer mortality at the township level. Results: Between 2017 and 2019, cancer mortality rates among women declined from 44.9 % to 42.0 %, while rates among men increased from 55.0 % to 57.9 %. The epicenter of mortality shifted from central regions in 2017 to western regions in 2018, then to eastern regions in 2019. The standard deviation ellipse indicated a transition in cancer mortality distribution from a northwest-southeast alignment in 2017 to predominantly western and eastern orientations in subsequent years, with varied hotspot patterns across Iran. Conclusions: The study highlights rising cancer mortality rates, particularly among men and premenopausal women, underscoring the need for targeted public health interventions and improved medical infrastructure to enhance prevention and treatment efforts.